2019
DOI: 10.1016/j.enbuild.2018.10.027
|View full text |Cite
|
Sign up to set email alerts
|

A study on thermal characteristic and sleeping comfort of a hybrid solar heating system applied in cold rural areas

Abstract: A study on thermal characteristic and sleeping comfort of a hybrid solar heating system applied in cold rural areas,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…To overcome those challenges, reference was made to Lin and Deng (2008), who measured total insulation values for bedding materials commonly used in subtropical environments by applying a selection of bedding, sleepwear, and mattresses to a prostrate thermal mannequin in an environmental chamber [15]. Their method has guided most recent research on sleeping environments [49], [50], [51], [52], [53], [54], [55], and [56], particularly in hospitals [32], [17], and [16]. Two combinations of garments (i.e.…”
Section: Fig 4 Standard Patient Room (Single Occupancy) Layout At Imc...mentioning
confidence: 99%
“…To overcome those challenges, reference was made to Lin and Deng (2008), who measured total insulation values for bedding materials commonly used in subtropical environments by applying a selection of bedding, sleepwear, and mattresses to a prostrate thermal mannequin in an environmental chamber [15]. Their method has guided most recent research on sleeping environments [49], [50], [51], [52], [53], [54], [55], and [56], particularly in hospitals [32], [17], and [16]. Two combinations of garments (i.e.…”
Section: Fig 4 Standard Patient Room (Single Occupancy) Layout At Imc...mentioning
confidence: 99%
“…For a novel solar energy heating system combining the solar thermal storage tank and the traditional Kang, the thermal storage tank without thermal insulation heats the room by natural heat dissipation, and the setting of the flue under the thermal storage tank can also make full use of the waste heat of the smoke [93]. Zhao et al [94] explored the practicability of a hybrid solar heating system combining a solar Kang subsystem and a solar air heating subsystem in rural buildings in Qinghai Province by field measurement and simulation. The results indicated that the indoor temperature of the test room can be improved by up to 6 • C when the ambient temperature was 7.8 • C (average), moreover, the area of collectors, thermal insulation, and an appropriate operation strategy were important factors.…”
Section: Solar Coupled Kangmentioning
confidence: 99%
“…In addition, the heating pattern of part time and part space is required in rural residences. To some extent, bed warming may be effective and suitable [94].…”
Section: Residential Demand Analysismentioning
confidence: 99%
“…In other words, the transmission of solar irradiation can be exploited to elevate indoor temperatures in cold weather. [ 6 ] Moreover, the reflection of solar irradiation can prevent indoor environments from undesired increases in temperature. To further decrease the temperature, it is possible to implement objects that can passively dissipate heat to outer space via the atmospheric long‐wave infrared (LWIR) transparency window (λ ≈ 8–13 µm).…”
Section: Introductionmentioning
confidence: 99%